Fluted and Basally Thinned Concave-Base Points of Obsidian in the Borden Collection from Inyo County, Alta California: Age and Significance. (2nd January 2018) - Moratto, Michael J.; Garfinkel, Alan P.; Erlandson, Jon M.; Rogers, Alexander K.; Rondeau, Michael F.; Rosenthal, Jeffrey; Skinner, Craig; Carpenter, Tim; Yohe, Robert M.
Abstract: This article describes, classifies, and provides the calculated ages of 14 basally thinned and fluted points of obsidian in the Borden collection from Rose Valley in southern Inyo County, California. With the exception of one item of Fish Springs obsidian, the specimens are all made of glass from geologic subsources in the Coso Volcanic Field. Typologically, the fragmentary and reworked artifacts appear to represent Clovis, or perhaps Clovis-derived, concave-base lanceolate points. Obsidian hydration measurements permit age calculations that range between approximately 13, 793 and 11, 308 calendar years ago. The calculated ages of the Borden artifacts are consistent with their discovery on landforms associated with Younger Dryas and very early Holocene wetlands. Our research results also suggest that Clovis technology may have persisted longer in California than it did in the southeastern, central, and southwestern United States.